Energy balance-related factors associating with adolescent weight loss intent: evidence from the 2017 National Youth Risk Behavior Survey - Ryan D. Burns (BMC, 2019)
Abstract Background The purpose of this study was to examine specific energy balance-related behaviors (sedentary behaviors, physical activity, and dietary) associating with adolescent weight loss intent using data from the 2017 US Youth Risk Behavior Survey (YRBS). Methods This was a cross-sectional study that employed a multi-stage cluster sampling procedure to obtain a representative sample of US adolescents. The target population consisted of public and private high schoolers from grades 9 through 12. The number of sampled adolescents was 18,324 with 14,765 of the 18,324 sampled students (Mean age = 15.9 (1.3) years) submitting questionnaires with usable data (81% response rate). The outcome was intent to lose weight with specific energy-balance related behaviors examined as predictor variables. A weighted logistic regression model was employed to examine the associations between sedentary behaviors, physical activity, and dietary-related variables with weight loss intent controlling for age, sex, BMI percentile, and race/ethnicity. Results Variables associating with adolescent intent to lose weight included 3 or more hours of video game playing (OR = 1.15, 95%CI: 1.01-1.31, p = 0.028), achieving 60 min of physical activity daily (OR = 0.66, 95%CI: 0.59-0.73, p < 0.001), daily breakfast consumption (OR = 0.76, 95%CI: 0.67-0.87, p < 0.001) and weekly salad consumption (OR = 1.30, 95%CI: 1.12-1.52, p = 0.001). Conclusions Meeting physical activity guidelines and regular breakfast consumption associated with lower odds of weight loss intent and video game playing and salad consumption associated with higher odds of weight loss intent in a representative sample of US adolescents. Therefore, there is a discordance between adolescent weight loss intent and the engagement in specific energy balance-related health behaviors, particularly physical activity.